2021
DOI: 10.1002/osp4.540
|View full text |Cite
|
Sign up to set email alerts
|

Improving lifestyle obesity treatment during the COVID‐19 pandemic and beyond: New challenges for weight management

Abstract: Objective The COVID‐19 pandemic has resulted in significant changes to daily life and many health‐related behaviors. The objective of this study was to examine how the stay‐at‐home/safer‐at‐home mandates issued in Colorado (March 2020–May 2020) impacted lifestyle behaviors and mental health among individuals with overweight or obesity participating in two separate behavioral weight loss trials ( n = 82). Methods Questionnaires were used to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 26 publications
2
27
0
1
Order By: Relevance
“…Our study has several limitations. First, our third study cohort was interrupted by COVID-19 at week 6 of the intervention, resulting in insignificant disruptions to the daily lives of our participants, as previously reported (34). The disruption to research also resulted in missing data (DXA, HbA1c, lipids, and REE) and required us to change the primary outcome from DXA weights to clinic and/ or home weights.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations. First, our third study cohort was interrupted by COVID-19 at week 6 of the intervention, resulting in insignificant disruptions to the daily lives of our participants, as previously reported (34). The disruption to research also resulted in missing data (DXA, HbA1c, lipids, and REE) and required us to change the primary outcome from DXA weights to clinic and/ or home weights.…”
Section: Discussionmentioning
confidence: 99%
“…Our study underscores the importance of behavioral support for successful weight loss, particularly in the face of stress and anxiety. We were able to adapt the delivery of our support to a virtual platform, and participants indicated that this helped them overcome some of the barriers to weight loss posed by the pandemic (5). In contrast to other studies reporting weight gain during the pandemic (4), our data show that, in the context of behavioral support, weight loss was not only possible but greater than previous cohorts in the same study.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that greater adherence to the intervention was due to higher motivation at baseline or greater group cohesiveness. Qualitative data from surveys in the COVID cohort have suggested that many participants found group support to be helpful in the face of the pandemic (5). The COVID cohort had lower cognitive restraint at baseline but similar restraint to the pre-COVID cohorts at 12 weeks; therefore, it is possible that changes in restraint contributed to improved weight loss in the COVID cohort, as previous dietary-intervention studies have shown that a greater increase in cognitive restraint during an intervention predicts greater weight loss (23,24).…”
Section: Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…With high rates of mental health conditions, food insecurity, and limited social support, veterans may be especially vulnerable to COVID-19–related behavior change and weight gain ( 14 – 18 ). Weight management programs, including MOVE!, may need to incorporate additional strategies to help participants overcome the challenges to modifying health behaviors in the context of heightened pandemic-related stress and anxiety ( 19 ).…”
Section: Discussionmentioning
confidence: 99%